Application of Inheritance Law in Minangkabau According to Islamic Law - Rahmadanil; Zuwanda, Rifka (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The majority of Minangkabau people give heirloom to their daughters, not to their sons. The heirloom that is passed down from generation to generation becomes a high heirloom, while the heirloom resulting from the work of parents becomes a low heirloom. High heirloom and low heirloom are different from the division of inheritance law in Islam. High heirloom is intended for daughters, low heirloom has the right of a sons in it (handed over to uncle as head of heirloom and he is responsible for the mandate given by parents). This empirical juridical research obtained data from document studies, interviews, and questionnaires. The results of the study show that Minangkabau society still uphold Islamic law because the guidelines in the application of inheritance distribution are sourced from sharia law, but the terms are different. In practice, high heirloom and low heirloom are on the same line as the inheritance law material. No one is harmed in its application, in accordance with the provisions stipulated by custom or Islamic law.